Grasses in Poland: invincible, but threatened - Frey, Ludwik (Biodiversity: Research and Conservation, 2011)
The paper presents problems connected with expansiveness and threats of grasses in Poland. Some subjectively selected grass species are given. They have conventionally been divided into two opposite groups: (i) expansive or even invasive grasses, referred to here as "invincible", and (ii) grasses that are threatened for a variety of reasons, and deserving protection.